Development and validation of a machine learning, smartphone-based tonometer. Issue 10 (23rd December 2019) - Wu, Yue; Luttrell, Ian; Feng, Shu; Chen, Philip P; Spaide, Ted; Lee, Aaron Y; Wen, Joanne C
Abstract : Background/Aims: To compare intraocular pressure (IOP) measurements using a prototype smartphone tonometer with other tonometers used in clinical practice. Methods: Patients from an academic glaucoma practice were recruited. The smartphone tonometer uses fixed force applanation and in conjunction with a machine-learning computer algorithm is able to calculate the IOP. IOP was also measured using Goldmann applanation tonometry (GAT) in all subjects. A subset of patients were also measured using ICare, pneumotonometry (upright and supine positions) and Tono-Pen (upright and supine positions) and the results were compared. Results: 92 eyes of 81 subjects were successfully measured. The mean difference (in mm Hg) for IOP measurements of the smartphone tonometer versus other devices was +0.24 mm Hg for GAT, −1.39 mm Hg for ICare, −3.71 mm Hg for pneumotonometry and −1.30 mm Hg for Tono-Pen. The 95% limits of agreement for the smartphone tonometer versus other devices was −4.35 to 4.83 mm Hg for GAT, −6.48 to 3.70 mm Hg for ICare, −7.66 to −0.15 mm Hg for pneumotonometry and −5.72 to 3.12 mm Hg for Tono-Pen. Overall, the smartphone tonometer results correlated best with GAT (R 2 =0.67, p<0.001). Of the 92 videos, 90 (97.8%) were within ±5 mm Hg of GAT and 58 (63.0%) were within ±2 mm Hg of GAT. Conclusions: Preliminary IOP measurements using a prototype smartphone-based tonometer was grossly equivalent to the reference standard.